TRANSFER OF HEAVY METALS IN SOIL IN-PLUM CULTIVATION: A FIELD STUDY IN ADAMACHI IASI, ROMANIA - Mariana RUSU; Irina Gabriela CARA; Manuela FILIP; Anca-Elena CALISTRU; Denis ȚOPA; Gerard JITĂREANU (Journal of Applied Life Sciences and Environment)
Currently, global environmental concerns about heavy metal pollution are driven by rapid urbanization and industrial development. Therefore, a field study was conducted to assess the concentration of heavy metals (Pb, Co, Zn, Ni and Cu) in orchard soils and its transfer to two plum varieties (Stanley and Anna Späth) at Adamachi Farm – Iasi University of Life Sciences (IULS). In addition, heavy metal transfer (MTF), daily metals intake (DIM) and the index of health risk (HRI) were evaluated. The concentration of Pb, Co, Zn, Ni and Cu in soil and plum leaves samples were analyzed using atomic absorption spectrometry after acid digestion with a mixture of HNO3 (65%), HCl (37%) and HClO4 (60%). Metal concentration patterns occurred as follows 130.65>76.6>30.36> 21.69>13.26 mg/kg for Cu, Zn, Ni, Pb and Co in soil samples and 20.16>10.00> 2.10>1.68 mg/kg for Zn, Cu, Ni and Pb in plum leaves, while Co residue was not detected. The maximum heavy metal concentrations were found at the soil surface (0 – 30 cm depth) due to soil organo-mineral content and antifungal treatments. The health risk index predicted (HRI) for adults as well as children was in the sequence Pb > Cu > Ni > Zn, suggesting no health risk with values that did not exceed the safe limit (1). Therefore, it is essential to manage the causes and sources of heavy metal transfer prudently and effectively in order to prevent environmental contamination.